Perfil empreendedor: um estudo sobre o empreendedorismo feminino na cidade de Manaus - Galvão, Emilly Pinheiro (Brasil, 2024)
Entrepreneurship has existed since the beginning of humanity, however, always with greater participation of the male gender, with the late insertion of women in the labor market, consequently, also in entrepreneurship there are peculiarities that differ female entrepreneurship from male entrepreneurship, which is the subject of several studies today. The general objective of this research is to analyze the success factors of female entrepreneurship in the city of Manaus. The methodology used is based on qualitative and descriptive research, operationalized through field research, using the interview method.At the end of this research, financial difficulties were identified as the most recurrent; women's ability to reconcile personal and family life, called "multitasking"; Sensitivity in management and technical training indicated as an essential factor for the success of women entrepreneurs in Brazil and local times.